POLA ASUH ORANG TUA, STATUS GIZI BALITA, DAN PERKEMBANGAN BALITA USIA 4-5 TAHUN DI PAUD DHARMA WANITA PERSATUAN PROVINSI BENGKULU - Nurul Khairani; Dirhan Dirhan; Abe Indriantama (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Short term impact of malnutrition on child development was the child will make apathy, speech disorders and other developmental disorders. While the long term impact was a decrease in intelligence quotient (IQ) scores, decreased cognitive development, decreased sensory integration, attention disraction, impaired confidence disorder and, of course, declining academic achievement in schools. The purpose of this study was to determine the Relationship of Parenting pattern and Nutrition Status of Toddler with Development of Toddler with Age of 4-5 Years in Early Childhood Education Program Dharma Wanita Persatuan Bengkulu Province. This study used survey analytic with cross sectional design. Sample in this study were all mother who had toddler with age of 4-5 years in Early Childhood Education Program Dharma Wanita Persatuan Bengkulu Province academic years 2017/2018 with the amount of 32 mothers of toddlers. Data analysis technique in this study used univariate and bivariate with Chi-Square test (χ2). The results of the study revealed that of the 32 toddlers there were 26 mothers of toddlers (81,3%) had parenting democratic parents, 25 mothers of toddlers (78,1%) had toddlers with good nutritional status, 28 mothers of toddlers (87,5%) who had toddlers with good development. There was not significant relationship between parenting pattern with development of toddler in early childhood education Program Dharma Wanita Persatuan Bengkulu Province. There was not significant relationship between nutrition status of toddler with development of toddler in early childhood education Program Dharma Wanita Persatuan Bengkulu Province. It was expected that parents can apply good parenting, meet nutritional needs and provide optimal stimulation of child development. Keywords: development of toddler, nutrition status of toddler, parenting pattern